Will the Increasing of Anthropogenic Pressures Reduce the Biopotential Value of Sponges? - Hedi Indra Januar; Asri Pratitis; Aditya Bramandito (Scientifica)
Production of bioactive compounds from marine benthic organisms is suggested to relate ecologically with environment. However, anthropogenic pressures cause a considerable damage to coral reefs environment. This research aimed to define the pattern sponges biopotential values at the increasing of anthropogenic pressures to coral reef environment. Three representative sponges were selected (Theonella sp., Hyrtios sp., and Niphates sp.) and study had been conducted in Hoga Island, Indonesia, to define the relationship between seawater variables (DO, pH, phosphate, and ammonia ions), sponges spatial competition, and their bioactivity level (Brine Shrimp Lethality Test). The study showed anthropogenic pressures affect the reef environment, as abiotic cover was increased and eutrophication was detected at the site closer to the run-off domesticated area. Statistical multivariate analyses revealed sponges spatial competition was significantly different (P<0.05) between groups of high, moderate, and low bioactivity level. Abiotic cover was detected as the major factor (36.19%) contributed to the differences and also the most discriminant factor distinguishing sponges spatial competition in the groups of bioactivity level (93.91%). These results showed the increasing anthropogenic pressures may result in a higher abiotic area and may directly be a consequence to the lower production of bioactive compounds in sponges.